Eficácia e segurança dos inibidores da ciclooxigenase celecoxibe e diclofenaco na periodontite induzida em ratos - Barroso, Márcia Vieira Barreira (2007)
Periodontitis is an inflammatory disease of the tissue that supports the teeth. It is caused by microorganisms and is characterized by leukocyte infiltration, progressive destruction of the periodontal ligaments, and alveolar bone. The clear role of prostaglandins on periodontal bone resorption has contributed to the rational use of the cyclooxygenase inhibitors drugs available. In this sense, it becomes necessary to bare safety and efficacy studies of the non-steroidal anti-inflammatory agents, such as celecoxib and potassium diclofenac. For the present study, a foreign object induced periodontitis model in rats was used, such as described on specific literature, to evaluate the activity of celecoxib and potassium and diclofenac. A surgical insertion of a nylon tread induced significant alveolar bone loss after 11 days. Celecoxib, given daily at 3, 9 and 27 mg/kg, significantly reduced this loss in a dose-dependent manner (64%, 53% and 75.4%, respectively). Diclofenac produced a similar effect at 1 and 5 mg/kg, reducing the loss by 41% and 54.5%, respectively. Macroscopic analyses of stomachs indicated that neither celecoxib nor diclofenac promoted gastric lesions when compared with non-treated animals. Celecoxib-treated rats did not show significant hemogram parameters alterations when subjected to periodontitis. For diclofenac-treated animals, it was verified a leukocytosis due to the augmentation of neutrophil count, which peaked between the 7th and the 11th day post-surgery. Platelet number of periodontitis-subjected animals, including those that received celecoxib or diclofenac treatment, was not altered, which may suggest that the doses used are relatively safe from the cardiovascular point of view, or that this alterations was not seen due to the short period of the study. Celecoxib and diclofenac were not able to significantly reverse the loss of body mass. The higher doses of diclofenac (10 and 25 mg/kg/day) significantly reduced the survival rate since the first day after surgery, reaching 50% at day 3. The induction of periodontitis in control and celecoxib-treated rats did not alter renal or hepatic function according to the biochemical parameters evaluated (urea and creatinine or AST). However, diclofenac, at 1 and 5 mg/kg/day, determined alterations in both kidney and liver functions, with a significant increase of seric levels of creatinine and AST. Diclofenac and celecoxib presented similar effects on bone loss prevention. Celecoxib, used for 11 days to induce periodontitis, was less toxic than diclofenac, which caused a dose-dependent mortality and leukogram alterations along with disruption of renal and hepatic functions.